Reconstruction of Criminal Responsibility for Misinterpretation of Radiological Images in Health Services Based on Legal Certainty and Substantive Justice - Yuki Mulyani; Faisal Santiago (International Journal of Social Service and Research, 2026)
The advancement of radiology technology has significantly transformed healthcare services through the use of digital imaging systems, Picture Archiving and Communication Systems (PACS), and teleradiology. However, the increasing complexity of radiological image interpretation has also raised legal issues, particularly regarding the determination of criminal responsibility for misinterpretation that causes patient harm. The absence of clear legal parameters distinguishing professional error, negligence, and criminal malpractice creates uncertainty for both radiologists and patients. This study aims to reconstruct the model of criminal responsibility for radiologists in cases of radiological image misinterpretation based on the principles of legal certainty and substantive justice. This research employed a normative juridical method using statutory and analytical approaches by examining criminal law regulations, health law provisions, legal doctrines, and professional standards in radiology practice. The results indicate that the current legal framework does not provide specific criteria for determining when radiological errors constitute criminal negligence. The study finds that not all diagnostic errors should be criminalized because radiology involves scientific interpretation and inherent medical risks. Therefore, criminal liability should only be imposed on cases involving gross negligence that significantly deviates from professional standards (lex artis). The reconstruction model emphasizes harmonization between criminal law and medical disciplinary mechanisms, the application of ultimum remedium principles, and the development of clearer legal guidelines. This approach is expected to ensure balanced protection for medical professionals and patients while strengthening justice and legal certainty in healthcare services